Range‐Wide Camera Trapping for the Australian Cassowary Reveals Habitat Associations With Rainfall and Forest Quality - Skye Elise Anderson; Zachary Amir; Tom Bruce; Matthew Scott Luskin (Ecology and Evolution, 2025)
ABSTRACT The Australian Wet Tropics rainforests are a biodiversity hotspot covering just 0.2% of the continent's land area. However, historic forest loss, modern fragmentation, and climate change continue to threaten these ecosystems. Southern cassowaries (Casuarius casuarius) are large flightless birds restricted to closed‐canopy tropical forests in Australia. Cassowaries are obligate frugivores whose dispersal of large‐seeded plants is considered a keystone species interaction supporting forest regeneration. We conducted camera trapping across cassowaries' Australian range and quantified habitat associations using hierarchical models that account for imperfect detection. Cassowary detections were significantly higher in rainforests compared to adjacent wet sclerophyll closed‐canopy forests, confirming their status as habitat specialists. Cassowaries' relative abundance (λ in Royle‐Nichols modelling) declined with forest degradation and rainfall but was not strongly affected by human footprint or elevation. This aligns with observations of them occasionally foraging on anthropogenic food sources at the edges of large intact forests (e.g., where there are human‐planted fruit trees). These findings provide the ecological reasons underpinning known cassowary hotspots in large rainforests that are relatively dry. It would be valuable to deepen our understanding of their persistence in degraded rainforests near humans via diet and survival studies, and we caution that their association with rainfall means that they may be impacted by climate change.